STUDI EKSPERIMENTAL PERBANDINGAN VARIASI SENGKANG MIRING TERHADAP KUAT GESER BALOK BETON BERTULANG - Arif Rachman Subiantoro; Rifa Aulia Bakri; Sri Tudjono; Han Ay Lie (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
Shear reinforcement in beams commonly known as reinforcement stirrups, vertical stirrup reinforcement, spiral reinforcement stirrups and stirrup bones tilted according to SNI-03-2847-2002 of the three types of vertical stirrup reinforcement is more commonly used in the concrete work because of the ease in implementation. For that the research will be carried out experimental studies comparing variations dash angled towards the shear strength of reinforced concrete beams. In this study will be made of 3 pieces slanted stirrups variations, ie sloping concrete beams cross bar welded middle (B2), sloping concrete beams cross bar latches satandar 135 ° (B3), concrete beam welding sloping top corner stirrups (B4) and 1 piece of concrete beams without cross bar that serves as a control beam (B1) with dimensions of beams used 100x200x2200 mm, the tests performed by a single point loading in the middle of the span. Based on the results of the 3 variations slanted stirrups, stirrups with slanting beam welding center (B2) was able to withstand the load Pu = 44.72 KN, shear force Vu = 22.84 KN and beam capacity rose 15.81%, sloping beams with stirrups standard hooks (B3) capable of withstanding the load Pu = 53.625 KN, shear force Vu = 27.29 KN and capacities up 38.89% beams, welded beams with stirrups sloping top corner (B4) capable of withstanding the load Pu = 54.580 KN, shear force Vu = 27.87 KN and beam capacity rose 41.88% of the beam without using stirrups.